Gefitinib in definitive management of esophageal or gastroesophageal junction cancer: a retrospective analysis of two clinical trials. Issue 6 (21st May 2014) - Sohal, D. P. S.; Rice, T. W.; Rybicki, L. A.; Rodriguez, C. P.; Videtic, G. M. M.; Saxton, J. P.; Murthy, S. C.; Mason, D. P.; Phillips, B. E.; Tubbs, R. R.; Plesec, T.; McNamara, M. J.; et al.
Summary The role of epidermal growth factor receptor inhibition in resectable esophageal/gastroesophageal junction (E/GEJ) cancer is uncertain. Results from two Cleveland Clinic trials of concurrent chemoradiotherapy (CCRT) and surgery are updated and retrospectively compared, the second study differing only by the addition of gefitinib (G) to the treatment regimen. Eligibility required a diagnosis of E/GEJ squamous cell or adenocarcinoma, with an endoscopic ultrasound stage of at least T3, N1, or M1a (American Joint Committee on Cancer 6th). Patients in both trials received 5‐fluorouracil (1000 mg/m2/day) and cisplatin (20 mg/m2/day) as continuous infusions over days 1–4 along with 30 Gy radiation at 1.5 Gy bid. Surgery followed in 4–6 weeks; identical CCRT was given 6–10 weeks later. The second trial added G, 250 mg/day, on day 1 for 4 weeks, and again with postoperative CCRT for 2 years. Preliminary results and comparisons have been previously published. Clinical characteristics were similar between the 80 patients on the G trial (2003–2006) and the 93 patients on the no‐G trial (1999–2003). Minimum follow‐up for all patients was 5 years. Multivariable analyses comparing the G versus no‐G patients and adjusting for statistically significant covariates demonstrated improved overall survival (hazard ratio [HR] 0.64, 95% confidence interval [CI] = 0.45–0.91, P = 0.012), recurrence‐free survival (HR 0.61, 95% CI = 0.43–0.86, P = 0.006), and distant recurrence (HR 0.68, 95% CI = 0.45–1.00, P = 0.05), but not locoregional recurrence. Although this retrospective comparison can only be considered exploratory, it suggests that G may improve clinical outcomes when combined with CCRT and surgery in the definitive treatment of E/GEJ cancer.